(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
The article shows the usage of STEAM (Science, Technology, Engineering, Arts and Mathematics) technologies in teaching English as a foreign language. It proves how incorporating STEAM technologies into English lessons can provide a holistic learning experience that fosters creativity, critical thinking, and interdisciplinary connections. Here are some ideas on how to integrate STEAM technologies into English lessons. The basis of modern approaches, the suggestions and recommendations for enhancing the information methodological support for the development of communicative, linguistic, sociolinguistic, pragmatic, speech and lexical competences with the help of STEAM technologies in teaching English are explained in the article.